The behaviours and night disturbances of the green turtle in Penang Island, Peninsular Malaysia - Sarahaizad Mohd Salleh,; Shahrul Anuar Mohd Sah, (Malaysian Society of Applied Biology, 2015)
This paper focuses on the observation and behaviours of green turtles for one breeding season at Penang Island. Green turtle breeding behaviours and morphological characteristics were studied at Pantai Kerachut and Teluk Kampi, situated at Penang Island, the northern island of Peninsular Malaysia between December 2012 and August 2013. The findings revealed that from the eight green turtles landed; 106 were emergences, 38 were nests, and 158 digging attempts were made over the duration of one breeding season. The total clutch size deposited ranged from 170 to 979 eggs per turtle, and total nests ranged from three to eight nests per turtle. The inter-nesting interval ranged from 9 to 29 days, and the average was 13.5 days. Longer inter-nesting intervals were due to disturbances from feral dogs, wild pigs, sea-coated otters and night activities of fishermen (use of wide torch lights, sounds of boat engines) especially at Teluk Kampi. Lack of full-time personnel to control at Teluk Kampi was found to be a cause to nest poaching. Based on these findings and observation, the study suggests that Kerachut Turtle Conservation Centre should hire sufficient staffs to patrol the two beaches in order to prevent from human poachers and animal disturbances.